Online learning communities and teacher professional development methods for improved education delivery - Lindberg, J. Ola, 1966-; Olofsson, Anders D., 1973- (Information Science Reference, 2010)
"This book features innovative applications for the integration of technology into everyday teaching practices"--Provided by publisher.